2017
DOI: 10.5194/acp-2017-1042
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Birch leaves and branches as a source of ice-nucleating macromolecules

Abstract: Abstract. Birch pollen are known to release ice-nucleating macromolecules (INM), but little is known about the production and release of INM from other tissues of the tree. We examined the ice nucleation activity of tissues from ten different birch 10 trees (Betula spp.). Samples were taken from nine birch trees in Tyrol, Austria, and from one tree in a small urban park in Vienna, Austria. Filtered aqueous extracts of 30 samples of leaves, primary wood (new branch wood, green in colour, photosynthetically acti… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2
1
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…However, not all biological INP are affected by heat. Materials from birch trees e.g., have been shown to be resistant towards heat treatment up to at least 100 • C [51,91]. Further it should be noted that the urea treatment can lead to a shift in pH value, as it can increase the pH value of aqueous systems and influences the dissociation of weak acids [92].…”
Section: Discussionmentioning
confidence: 99%
“…However, not all biological INP are affected by heat. Materials from birch trees e.g., have been shown to be resistant towards heat treatment up to at least 100 • C [51,91]. Further it should be noted that the urea treatment can lead to a shift in pH value, as it can increase the pH value of aqueous systems and influences the dissociation of weak acids [92].…”
Section: Discussionmentioning
confidence: 99%
“…This study site is free from traffic emissions since it is located in the middle of the Austrian Alps surrounded by mountains. Many native birches of the species Betula pendula grow next to the lake (Figure 3b), making it attractive for field studies on biological INP emissions, since pollen, leaves and wood of Betula pendula contain INPs [17,22]. We divided sampling spots into three different areas (Figure 3c).…”
Section: Study Sitementioning
confidence: 99%
“…Pummer et al showed that INPs of pollen grains can also be in the macromolecular size range [17]. Experiments with birch branches, bark, leaves and pollen have highlighted the possibility of ice nucleation macromolecules (INMs) to be extracted from plant tissues with water [22]. Thus, ice-nucleating BAPs may be generated during rainfall events when droplets impact on tree surfaces and/or leaf litter [23].…”
Section: Introductionmentioning
confidence: 99%
“…Line 69: Please include the following references: Felgitsch et al 2018, Kunert et al 2019, Pummer et al 2015 Line 98: Please add the following reference: Kunert et al 2018. Lines 98f: It would be nice if the authors could elaborate a bit more on advantages and disadvantages of the different methods.…”
Section: Specific Commentsmentioning
confidence: 99%